2017
DOI: 10.1001/jamaoncol.2016.4280
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Concurrent Use of Thoracic Radiation With Either Carboplatin-Paclitaxel or Cisplatin-Etoposide for Patients With Stage III Non–Small-Cell Lung Cancer

Abstract: Cisplatin-etoposide and carboplatin-paclitaxel regimens were associated with comparable efficacy when used with concurrent definitive radiotherapy for patients with stage III unresectable NSCLC. The toxic effect profiles favored the carboplatin-paclitaxel regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 73 publications
1
50
0
1
Order By: Relevance
“…A systematic review and Veterans’ Health Administration data in the United States showed that carboplatin plus paclitaxel compared with etoposide plus cisplatin did not increase the risk of radiation pneumonitis in dCRT for stage III non–small-cell lung cancer. 26 , 27 However, retrospective studies have indicated that paclitaxel-based dCRT did significantly increase the risk of radiation pneumonitis, with an odds ratio of 3.33. 28 , 29 Liang et al 30 recently published a phase III trial that compared etoposide plus cisplatin with carboplatin plus paclitaxel in dCRT for patients with stage III non–small-cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and Veterans’ Health Administration data in the United States showed that carboplatin plus paclitaxel compared with etoposide plus cisplatin did not increase the risk of radiation pneumonitis in dCRT for stage III non–small-cell lung cancer. 26 , 27 However, retrospective studies have indicated that paclitaxel-based dCRT did significantly increase the risk of radiation pneumonitis, with an odds ratio of 3.33. 28 , 29 Liang et al 30 recently published a phase III trial that compared etoposide plus cisplatin with carboplatin plus paclitaxel in dCRT for patients with stage III non–small-cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Lower dose parameters such as lung V5 have in some studies been correlated with higher risk of lung toxicity with either conventional RT or SBRT [95,96]. A systematic review showed that cisplatin or carboplatin-based chemotherapy can be used safely with concurrent chest radiotherapy [6,97]. Predictors of grade 5 pneumonitis were daily dose >2 Gy, V20 and lower-lobe tumour location.…”
Section: Dose-volume Constraints (Tables 2 and 3)mentioning
confidence: 99%
“…Only 4 patients were diagnosed as local recurrence confirmed by imaging and / or pathology and 3 of them died from the following causes: myelosuppression grade IV, sudden cardiac death, hemoptysis. The result showed that the ORR was kept at 90% by SIB-IMRT which was superior to the result of chemotherapy and conventional fractionated radiotherapy for local advanced NSCLC [26] . It may be due to the increase of ORR, the proportion of tumor shrinkage and regression increased ,which was beneficial to reduce the recurrence and mortality rate and positively correlated with the prolongation of survival rate [4] The OS and LPFS rates at 1, 3 and 5 years were 90%, 42.6%, 35.5% and 84.4%, 35.5%, 28.4%, respectively.…”
Section: Discussionmentioning
confidence: 90%